15N Metabolic Labeling Quantification Workflow in Arabidopsis Using Protein Prospector - Shrestha, Ruben; Reyes, Andres V.; Baker, Peter R.; Wang, Zhi-Yong; Chalkley, Robert J.; Xu, Shou-Ling (Frontiers in Plant Science, 2022)
Metabolic labeling using stable isotopes is widely used for the relative quantification of proteins in proteomic studies. In plants, metabolic labeling using 15N has great potential, but the associated complexity of data analysis has limited its usage. Here, we present the 15N stable-isotope labeled protein quantification workflow utilizing open-access web-based software Protein Prospector. Further, we discuss several important features of 15N labeling required to make reliable and precise protein quantification. These features include ratio adjustment based on labeling efficiency, median and interquartile range for protein ratios, isotope cluster pattern matching to flag incorrect monoisotopic peak assignment, and caching of quantification results for fast retrieval.